2014
DOI: 10.1007/s10295-014-1473-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ascomycin production in Streptomyces hygroscopicus var. ascomyceticus by combining resin HP20 addition and metabolic profiling analysis

Abstract: Combinatorial approach of adsorbent resin HP20 addition and metabolic profiling analysis were carried out to enhance ascomycin production. Under the optimal condition of 5 % m/v HP20 added at 24 h, ascomycin production was increased to 380 from 300 mg/L. To further rationally guide the improvement of ascomycin production, metabolic profiling analysis was employed to investigate the intracellular metabolite changes of Streptomyces hygroscopicus var. ascomyceticus FS35 in response to HP20 addition. A correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Recently, considerable efforts have been made to enhance the ascomycin titer of the production strains, including random mutagenesis and selection [ 7 ], fermentation technology optimization [ 8 ], comparative metabolic profile analysis [ 9 ], and so on. However, the relatively low yield of ascomycin in bio-fermentations is still a major obstacle for its further industrialization and commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable efforts have been made to enhance the ascomycin titer of the production strains, including random mutagenesis and selection [ 7 ], fermentation technology optimization [ 8 ], comparative metabolic profile analysis [ 9 ], and so on. However, the relatively low yield of ascomycin in bio-fermentations is still a major obstacle for its further industrialization and commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, metabolic pro ling analysis showed that lysine (Lys), used for the synthesis of precursors pipecolic, and valine (Val), used for the synthesis of precursors methylmalonyl-CoA, were the key primary metabolites in the production of FK520 under the condition of adding resin HP20. Adding 1.0 g/L Val to the fermentation broth at 48 h increased the yield of FK520 by 9.2 %, and adding 1.0 g/L Lys at 72 h increased the FK520 yield by 13.2 % [2]. Similarly, another previous research showed that for the shikimic acid-resistant strain SA68, adding 3 g/L shikimic acid, an important metabolite used for the synthesis of precursor DHCHC, to the fermentation broth at 48 h increased the yield of FK520 by 36 % [45].…”
Section: Discussionmentioning
confidence: 99%
“…ascomyceticus FS35 selected from S. hygroscopicus var. ascomyceticus ATCC 14891 after femtosecond laser irradiation was used as the parent strain [2]. All the strains and plasmids used in this work are listed in Additional le 1: Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] To date, only few studies exist in the literature that demonstrate the application of targeted GC-MS analysis of metabolites for the optimization of fermentation medium and parameters in industrial scale biomass productions. [13,14] The aim of the present study was to evaluate dynamics of the broth metabolome of a large industrial production scale fermentation with S. thermophiles using untargeted GC-MS metabolomics. Seven different batch fermentations were screened for the change of metabolites during the fermentation time.…”
Section: Introductionmentioning
confidence: 99%